OECD Unbundled Local Loop Pricing - Madden, Gary; Bohlin, Erik; Ahmad, Hasnat; Tran, Thien (Pergamon, 2013)
This study examines OECD fully unbundled and line sharing monthly wholesale prices for 2002–2008. The results are informative with economic analysis appearing to inform regulator decision making. However, with the cost proxy (viz.,copper-wage relative price, population density, urbanisation and business line penetration),regulator costing methods (long run incremental and fully allocated cost), and time trend arguments only explaining approximately 40% of the price variation there remains ample unexplained variation, and political and institutional variables may help reduce this. Finally, both price series are subject to increasingly rapid value declines, although the patterns are somewhat distinct. This suggests that initial prices are truly transitory.